Moringa oleifera Aqueous Leaf Extract Induces Cell-Cycle Arrest and Apoptosis in Human Liver Hepatocellular Carcinoma Cells. (3rd October 2019) - Tiloke, Charlette; Phulukdaree, Alisa; Gengan, Robert M.; Chuturgoon, Anil A.
Abstract: Aim: Hepatocellular carcinoma is one of the leading global epidemics. A medicinal tree, Moringa oleifera (MO), has been part of traditional treatments including cancer therapies. We investigated the apoptosis inducing effects of MO crude aqueous leaf extract (MOE) in human liver hepatocellular carcinoma (HepG2 ) cells. Methods: HepG2, PBMCs and Hek293 cell viability was evaluated using MTT assay. Oxidative stress and DNA damage was determined using TBARS and comet assays, respectively. Apoptosis was assessed by caspase-9, -3/7 activities and ATP levels (luminometry). Cell cycle, γH2AX, and cleaved PARP-1 were determined (flow cytometry). Protein expression of c-myc, Bax, p-Bcl2, Smac/DIABLO, Hsp70, SRp30a and cleaved PARP-1 was assessed using western blotting. Results: MOE displayed minimal toxicity in PBMCs and Hek293 cells for 24 h. HepG2 cells were exposed to MOE (24 h) and an IC50 (4.479 mg/mL) was determined. MOE significantly increased lipid peroxidation, DNA damage and γH2AX levels. A significant decrease in G1, S and G2-M phase was seen. Significant increase in SRp30a protein expression activated caspase-9. Caspase-9 and -3/7 was significantly increased with significant decrease in ATP levels. Apoptosis was confirmed with significant decrease in c-myc, p-Bcl2 and Hsp70 protein expression and a significant increase in Bax, Smac/DIABLO and PARP-1 cleavage. Conclusion: MOE induces cell-cycle arrest and apoptosis in cancerous HepG2 cells.